2010
DOI: 10.1016/j.cell.2010.01.026
|View full text |Cite
|
Sign up to set email alerts
|

The Angelman Syndrome Protein Ube3A Regulates Synapse Development by Ubiquitinating Arc

Abstract: Angelman Syndrome is a debilitating neurological disorder caused by mutation of the E3 ubiquitin ligase Ube3A, a gene whose mutation has also recently been associated with autism spectrum disorders (ASDs). The function of Ube3A during nervous system development, and how Ube3A mutations give rise to cognitive impairment in individuals with Angleman Syndrome and ASDs are not clear. We report here that experience-driven neuronal activity induces Ube3A transcription and that Ube3A then regulates excitatory synapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
571
6
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(601 citation statements)
references
References 45 publications
20
571
6
4
Order By: Relevance
“…The ubiquitin ligase enzyme Ube3A is a member of the E3 ubiquitin ligase family. The disruption of its activity leads to Angelman syndrome, while in turn the Angelman syndrome was described in ASD with CNVs and mutations in UBE3A gene (Greer et al., 2010). In Ube3A knockout mice, electrophysiological studies demonstrated an impaired long‐term potentiation (LTP) in the hippocampus, which suggest that alteration of Ube3A results in the loss of neuronal plasticity.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitin ligase enzyme Ube3A is a member of the E3 ubiquitin ligase family. The disruption of its activity leads to Angelman syndrome, while in turn the Angelman syndrome was described in ASD with CNVs and mutations in UBE3A gene (Greer et al., 2010). In Ube3A knockout mice, electrophysiological studies demonstrated an impaired long‐term potentiation (LTP) in the hippocampus, which suggest that alteration of Ube3A results in the loss of neuronal plasticity.…”
Section: Reviewmentioning
confidence: 99%
“…In fact, Ube3A increases transcription through the myocyte enhancer factor 2 (MEF2) complex and regulates synapse function by ubiquitinating and degrading the synaptic protein Arc (activity‐regulated cytoskeleton‐associated protein). The role of Arc is to decrease long‐term potentiation by promoting the internalization of AMPA receptors, which are the mediators of the excitatory neurotransmission in the central nervous system (Greer et al., 2010). On another hand, a decrease in AMPAR expression at synapses has been observed in patients with fragile X syndrome.…”
Section: Reviewmentioning
confidence: 99%
“…Given that the ligase activity is important for the ubiquitination and degradation of target proteins, these observations suggest that disruption of UBE3A activity leads to inappropriately high levels of these target proteins and consequent neuronal dysfunction. While several candidate substrates have been discovered, AS-relevant targets leading to neural defects after UBE3A loss have yet to be identified [61,62]. In addition, because UBE3A lies within a region of chromosome 15 that is duplicated in a subset of heterogeneous ASDs, it remains possible that altered levels of UBE3A substrates might be a mechanism relevant to the etiology of autism [34,63].…”
Section: Cellular and Molecular Underpinnings Of Asmentioning
confidence: 99%
“…Recent studies using Drosophila melanogaster have identified potential fly Dube3a substrates [64]. In an attempt to take an unbiased approach to identify AS-relevant substrates of Ube3a, several laboratories have tried to compare the complement of ubiquitinated proteins in AS mouse brains with wild-type brains using quantitative mass spectrometry [52,62,65]. It is unclear from the results of these studies which substrates are affected directly or indirectly by Ube3a.…”
Section: Cellular and Molecular Underpinnings Of Asmentioning
confidence: 99%
“…One UBE3A target, activity-regulated cytoskeleton-associated protein, mediates surface expression of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors (AMPARs) at excitatory synapses. In the absence of UBE3A expression, activity-regulated cytoskeleton-associated protein degradation is decreased, resulting in increased internalization of AMPARs and the development of impaired circuit function [25]. It has also been demonstrated that UBE3A plays a role in inhibitory synaptic function within the neocortex.…”
Section: Angelman Syndromementioning
confidence: 99%